American Creative Nonfiction - Elllis, Jay; Ellis, Jay, 1963- (Amenia, NY, Grey Publishing House, 2015, 2015)
This collection of critical essays on the American creative nonficition features an overview of the genre and critical readings of selected works and authors.
About this volume / Jay Ellis -- On American creative nonfiction / Jay Ellis -- American creative nonfiction : background and history / Kelly Clasen -- Critical reception of "a special kind of fiction" / Ross Griffin -- The lyric essay as non-nonfiction / Jay Ellis -- "Loops and spins" : autobiography, autofiction, and Tim O'Brien's serial selves / David Bahr -- Benjamin Franklin's middle way and the argumentative nature of autobiography / Peter Kratzke -- Gender and genre in Susan Fenimore Cooper's nature writing / Kelly Clasen -- "A canticle of my reaction" : socio-cultural criticism in Claude McKay's A long way from home / Christopher Allen Varlack -- "I'm fighting because you're down here" : small stories and big histories in Shelby Foote's The Civil War / Christopher Walsh -- Medical humanities and illness narratives / G. Thomas Couser -- The grand memoir : Temple Grandin and autism / Katherine Lashley -- Stories of the self in cinema : autobiography and the documentary image / Shira Segal -- One life transformed : Natalie Goldberg's writing, art, and religion / Beth Walker -- David Foster Wallace and the ethical potential of creative nonfiction / Brandon Benevento -- Choreographing time : Art Spiegelman's present, past(s) and the craft of creative nonfiction comics / David Bahr.
Edition statement supplied by publisher.
Includes bibliographical references and index.
Keywords: Creative nonfiction, American -- History and criticism; Authors, American -- Biography -- History and criticism; Narration (Rhetoric) -- History